2022
DOI: 10.3390/diagnostics12030719
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Varying Interval Definitions on the Prevalence of SARS-CoV-2 Reinfections: A Retrospective Cross-Sectional Cohort Study

Abstract: Background: We assessed the SARS-CoV-2 reinfection rate in a large patient cohort, and evaluated the effect of varying time intervals between two positive tests on assumed reinfection rates using viral load data. Methods: All positive SARS-CoV-2 samples collected between 1 March 2020 and 1 August 2021 from a laboratory in the region Kennemerland, the Netherlands, were included. The reinfection rate was analyzed using different time intervals between two positive tests varying between 2 and 16 weeks. SARS-CoV-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Wang et al (2021) in Asia, Europe, North America and South America found an average interval between the first Covid-19 infection and the second Covid-19 infection, an average of 76 days. Another study conducted by Pinto et al (2021) reported the characteristics of the time span of repeated infections, which were found to report 27 cases of re-infection with COVID-19, the duration between the first and second episodes was 108 days with a median of 60 days while Euser (2022) found eight weeks (2 months) between two positive PCRs can be defined for Covid-19 re-infection (Euser, 2022). Re-infection of SARS-Cov-2 is thought to occur after antibody titers decrease (Mulder et al, 2021).…”
Section: Distribution Of Covid-19 Time Rangementioning
confidence: 99%
“…Wang et al (2021) in Asia, Europe, North America and South America found an average interval between the first Covid-19 infection and the second Covid-19 infection, an average of 76 days. Another study conducted by Pinto et al (2021) reported the characteristics of the time span of repeated infections, which were found to report 27 cases of re-infection with COVID-19, the duration between the first and second episodes was 108 days with a median of 60 days while Euser (2022) found eight weeks (2 months) between two positive PCRs can be defined for Covid-19 re-infection (Euser, 2022). Re-infection of SARS-Cov-2 is thought to occur after antibody titers decrease (Mulder et al, 2021).…”
Section: Distribution Of Covid-19 Time Rangementioning
confidence: 99%
“…Moreover, there is still no clear global definition of SARS-CoV-2 reinfection. Some studies defined reinfection as the time interval between two positive tests needing to be more than 90 days [ 16 , 17 ], while some studies defined reinfection as the time interval only needing to be more than 30 days [ 18 , 19 ], and it was difficult to directly compare reinfection rates under different definitions with large differences [ 20 ]. Therefore, the aim of this study was to conduct a meta-analysis to describe and summarize the current reinfection rates in different regions and among diverse populations.…”
Section: Introductionmentioning
confidence: 99%